2010
DOI: 10.4028/www.scientific.net/msf.645-648.685
|View full text |Cite
|
Sign up to set email alerts
|

Significant Improvement in Reliability of Thermal Oxide on 4H-SiC (0001) Face Using Ammonia Post-Oxidation Annealing

Abstract: The effect of ammonia (NH3) post-oxidation annealing (POA) technique on the reliability of thermal oxides grown on a n-type 4H-SiC (0001) face by dry oxidation has been investigated. Comparing other POA techniques using hydrogen and nitrous oxide gases, it was indicated that the NH3 POA after dry oxidation remarkably improves the insulating properties of thermal oxides. The mode value of field-to-breakdown for thermal oxides prepared by NH3 POA was 12.1 MV/cm. The charge-to-breakdown (QBD) in the NH3 POA sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 4 publications
(4 reference statements)
0
16
1
Order By: Relevance
“…Moreover, the leakage current level of MOS capacitors on both crystal faces changed after NO-POA. The observed trend that F−N current decreases by nitridation on Si-face may look different from the previously reported trend of J G at room temperature for various nitridation processes, 14) but they cannot be directly compared to each other because J G at room temperature tends to be significantly affected by P−F emission currents. We calculated the effective barrier height of electrons for each MOS capacitor by using Eq.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, the leakage current level of MOS capacitors on both crystal faces changed after NO-POA. The observed trend that F−N current decreases by nitridation on Si-face may look different from the previously reported trend of J G at room temperature for various nitridation processes, 14) but they cannot be directly compared to each other because J G at room temperature tends to be significantly affected by P−F emission currents. We calculated the effective barrier height of electrons for each MOS capacitor by using Eq.…”
contrasting
confidence: 99%
“…3,4) The introduction of various foreign atoms to the interface 5) and H 2 O-POA is considered as a good technique to obtain better interface quality, [6][7][8] however, nitridation processes with NO, N 2 O or NH 3 gases are well-known beneficial techniques for the reduction of the interface trap density (D it ) of thermal-SiO 2 /4H-SiC interfaces on various crystal faces including (0001), ( ) 0001 , ( ) 1100 and ( ) 1120 and improves the performances of MOSFETs. [9][10][11][12][13][14] Recently we reported that NO-POA could have unexpected effects on the SiO 2 /4H-SiC (0001) band alignment, 15) which is one of the most important properties to determine the gate leakage currents (J G ). This is attributable to a dipole layer formation that causes abrupt change of electrical potential in hundreds of mV.…”
mentioning
confidence: 99%
“…In fig 3(a), NO nitrided oxide samples have larger amount of electron traps than the as-oxidized sample. This result suggests the electrons are captured by the near-interface traps in the NO nitrided oxide during F-N injection because the acceptor-like deep interface traps have already been filled with electrons [10]. The slope of the curves decreases with increasing NO POA time and the △Q trap in the oxide was greatly suppressed by NO POA for 3 hours as compared with the NO POA for 1, 2 hours.…”
Section: Resultsmentioning
confidence: 90%
“…2,3) Many research teams have worked to enhance channel mobility by improving the SiC MOS interface. [4][5][6][7][8][9][10][11] As a result, a solution that reduces the SiC MOS interface defects effectively was reported recently. [12][13][14] As a new approach to improving mobility, the research described in this paper focuses on strain engineering.…”
Section: Introductionmentioning
confidence: 99%